1987
DOI: 10.1007/bf00166463
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA rearrangements in Pennisetum associated with reversion from cytoplasmic male sterility to fertility

Abstract: Endonuclease restriction fragment patterns of Pennisetum americanum L. mitochondrial DNAs (mtDNAs) from a cytoplasmic male-sterile (CMS-A1), fertile revertants and a normal fertile cytoplasm were variable, while chloroplast DNA from those lines lacked variation. Comparisons between mtDNAs of CMS-A1 (parental) and fertile revertant lines revealed the presence of a unique 4.7 kbp PstI fragment in the sterile line that was not detected in any of the revertant lines. A 9.7 kbp PstI fragment was found in all of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Mitochondrial DNA rearrangements are often observed in some CMS systems upon reversion to fertility ( Fauron et al , 1987 ; Smith et al , 1987 ; Escotecarlson et al , 1988 ; Mackenzie et al , 1988 ; Bellaoui et al , 1998 ; Janska et al , 1998 ), with dramatic reduction in relative copy number of the CMS sequence in each case. Here, we demonstrated that the SSS of CMS-associated ORF220 occurs in association with fertility reversion in CMS B. juncea .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial DNA rearrangements are often observed in some CMS systems upon reversion to fertility ( Fauron et al , 1987 ; Smith et al , 1987 ; Escotecarlson et al , 1988 ; Mackenzie et al , 1988 ; Bellaoui et al , 1998 ; Janska et al , 1998 ), with dramatic reduction in relative copy number of the CMS sequence in each case. Here, we demonstrated that the SSS of CMS-associated ORF220 occurs in association with fertility reversion in CMS B. juncea .…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the representation of cpDNA in both libraries we hybridized one high-density filter from each library (18,432 clones) with a 1,900-bp fragment amplified between the trnH and trnK primers (Demesure et al 1995). Correcting for the insert size of the libraries and for an approximate chloroplast genome size in P. glaucum of 120 kb (Smith et al 1987), an estimated 0.1% and 0.7% of clones are of chloroplast origin in the polyhaploid and buffelgrass libraries, respectively. The proportion of mitochondrial clones were estimated at 0.2% and 0.5% in polyhaploid and buffelgrass libraries, respectively.…”
Section: Construction and Characterization Of The Librariesmentioning
confidence: 99%
“…No transcript variation was observed either in the leaves or spikelets or upon restoration of A and A cytoplasms (HA and HA ). Smith et al (1987) reported identifying and cloning fragments that were rearranged upon reversion of the A CMS cytoplasm to fertility. Four PstI fragments were cloned: a 4.7 kbp fragment found only in the A CMS line, a 9.7 kbp fragment found in 81B and in eight fertile revertants of the A cytoplasm, a 13.6 kbp fragment found in 81A , 81B and one revertant and a 10.9 kbp fragment found in all cytoplasms.…”
Section: A a A And A Cytoplasmic Groupmentioning
confidence: 99%